A new μ-patterning method for Carbon Nanotube (CNT) forest and its remarkable optical transformation - Saleh, Tanveer (2013)
Vertically aligned Carbon Nanotubes (CNTs) which are commonly referred to as CNT forests, have many potential engineering applications for its attractive mechanical, electrical, optical, and thermal properties. Patterning of CNT forests is very important to make them useful for different applications. Growing CNT forests selectively by chemical vapor deposition (CVD) on pre-patterned catalyst on the substrate is the most widely used technique to produce patterned CNT forest. However, there are difficulties associated with the production of 3-D -structures. A new -Electro-discharge Machining EDM) method was also proposed for patterning CNT forest to minimize this problem. However, EDM has inherent limitation of spark gap which cannot be completely eliminated. In this paper a novel method is described which uses a metallic tool to bend CNTs selectively on a CNT forest to create different patterns. The problem of spark gap of -EDM can thus be eliminated by this technique.The most significant observation made from the processed CNT forest is the visible optical reflection from bent and flattened area. Typically, CNT forest is known to be the darkest material on earth. However, new processing technique causes the CNT surface to reflect light like mirror. The reflectivity is measured to be in a range of 10% to 15% from visible to infrared spectrum of light. Unlike the conventional mirror, CNT mirror is found to be anisotropic and sensitive to the polarization of the light. Further, surface characterization like Scanning Auger Microscopy and Raman analysis ensures that processed surface is free from any contamination and crystalline defects that may occur from the new patterning method.